The green model of the Church : a theological response to the modern ecological crisis for a meaningful social change - Vayalil, Jose Mathew (New Delhi : Christian World Imprints, 2018)
The Church is defined in terms of models. None of the existing models of the Church have incorporated ecological concerns into it's theological framework. Therefore, there is a lack of a model of the Church that incorporates ecological concerns of the time. `The Green Model of the Church' fills a lacuna in Catholic ecclesiology. It is an appropriate theological response to the ecological crisis of our times. In other words, the book is an attempt to read the Church from the perspective of an eco-theologian. It is a green reading of the Church dogmas. Theology is both, faith seeking understanding and faith seeking intelligent action. Theology is not for showcasing but for intelligent action aimed at social change. The purpose of this scholarly work is to build a bridge between biological sciences and theological sciences towards a meaningful social change. It will be of use to those who function at the grass-root level, in the sphere of ecology and the Church--Jacket.
The contextual basis of the new model : ecological crisis -- The church and the environment -- The five waves of eco-philosophy -- Biblical and patristic basis for the Green Model -- The Green Model of the church -- Greening the Christian life : towards an ecclesiological praxis and a remedial praxis -- General synthesis and conclusions.
Keywords: Human ecology -- Religious aspects -- Christianity; Nature -- Religious aspects -- Christianity; Ecotheology; Ecotheology; Human ecology -- Religious aspects -- Christianity; Nature -- Religious aspects -- Christianity; Eco- Philosophy; Eco- Feminism; Green Ecclesiology